Learning Styles of Postgraduate Students at Shahid Beheshti Dental School Using VARK Questionnaire : The Learning Styles by Using VARK Questionnaire - Jafari, Soudeh; Mehdipour, Masoumeh; Mohamadi, Amireissa; Taheri, Jamileh Beigom; Dalirani, Sara (Journal of Dental School, 2024)
Objectives Learning clinical sciences is challenging for medical students and requires a wide range of knowledge and skills in the clinical environment. There are several ways to learn, and choosing the best can be very effective in a student’s learning success. Therefore; in this study, the learning styles of postgraduate students at Shahid Beheshti Dental School were evaluated. Methods The study was performed on 92 postgraduate students at Shahid Beheshti Dental School. The data analysis tool was the VARK questionnaire, and the data obtained were analyzed using descriptive tests. The learning styles among the gender and age groups were comprised using Chi-square (Exact test) at p<0.05. Results Among the mentioned learning methods, the kinesthetic method had the highest frequency, followed by the auditory and visual methods. Auditory-reading-writing- kinesthetic and visual-reading-writing were the least common. Moreover, there was no significant difference between the distribution of learning styles among men and women (p = 0.67) and different age groups (p = 0.7). Conclusion According to the results obtained from this study on the superiority of kinesthetic learning style among postgraduate dental students, it seems necessary for the educational system's officials and managers to plan appropriately for this group of learners' learning conditions to improve the quality of education.